Acrylamide in heat-treated carbohydrate-rich foods in Turkey - Dagoglu, Irem; Keskin Alkac, Zeliha; Korkak, Fatih Ahmet; Kazdal, Saibe Merve; Dag, Ayhan (Taylor & Francis Ltd, 2024)
This study was conducted to provide data on the amount of acrylamide (AA) in 270 heat-treated carbohydrate-rich foods in Turkey, determined by gas chromatography-mass spectrometry (GC-MS). A total of 270 samples were analysed and it was found that 85% of potato chips, 80% of biscuits, 85% of cakes, 80% of bread, 80% of roasted peanuts, 80% of roasted nuts and 85% of pretzels contained AA above the limit of quantification (LOQ). Analytical results indicated that 10 corn chips samples, 4 biscuits samples, all bread samples, all wheat bread samples, 2 dried bread samples and 1 pretzel sample contained AA levels above the benchmark levels of 150, 350, 50, 50, 300 and 300 mu g/kg, respectively, as set by the European Commission.
Keywords: Acrylamide; food; Turkey